Magnitude of fluorosis and various interventions to reduce fluorosis in Gujarat, India - Sangita V Patel; Kedar Gautambhai Mehta; Prakash V Kotecha (Wolters Kluwer Medknow Publications, 2020)
Background: Gujarat is one of the endemic states for the prevalence of fluorosis due to high fluoride levels in water of many villages in the state. Aim and Objectives: To determine the prevalence of dental fluorosis and skeletal fluorosis in Vadodara district, Gujarat, India, and to document various interventions conducted by Government to reduce the prevalence of fluorosis in Gujarat. Materials and Methods: A cross sectional survey was carried out in 11 villages (6 with high fluoride level and 5 with normal fluoride level) by house to house visits. Various interventions like capacity building of faculties, diagnostic, treatment and counseling for fluorosis and alternate water supply facilities were provided. Results: The prevalence of dental fluorosis and skeletal fluorosis was 59.31% and 18.65% in high fluoride areas, while it was 39.21% and 12.54% in normal fluoride areas, respectively. After estimation of this problem, and other research studies carried in Gujarat, the Government of Gujarat provided a fluorine meter to measure the fluoride level in water and urine in all government medical colleges of the state. Capacity building of faculties from various departments was done regarding the epidemiology, diagnosis, treatment, and counseling of fluorosis patients. Early diagnosis and treatment were provided to all fluorosis patients visiting tertiary care hospitals. Alternate drinking water supply was also provided by the government. Conclusion: Both dental and skeletal fluorosis was high in Gujarat and field level diagnostic facilities are inadequate. A coordinated training program helped to identify the problem and suggest remedial measures. An integrated and comprehensive approach is required to reduce the problem of fluorosis in Gujarat.